Spatial plans as tools for inland excess water prevention in Hungary - Szilassi, Péter (4D Journal of Landscape Architecture and Garden Art, 2015)
Inland excess water is a reoccurring problem on the Great Hungarian Plain with major economic and environmental consequences. On average, in Hungary, every year 110000 acre of land is covered with inland excess water. The total area that was flooded in 2010 reached 355000 acre and the estimated financial damage to the agriculture alone exceeded 500 million Euros. In Hungary due to the climate change we should preparing to the more frequency of extreme weather events, and inland excess water inundations. Spatial planning system must be one of the most important tool for the mitigation of climate change, and the planning of the optimal land use structure.
Keywords: spatial plans; tools; excess water